Growing Stock Volume Estimation in Temperate Forested Areas Using a Fusion Approach with SAR Satellites Imagery - Ackermann, Nicolas (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
"The PhD thesis written by Mr. Ackermann is an outstanding and in-depth scientific study that closes a research gap and paves the way to new developments. Despite the extremely complex issues, his work is very understandable and excellently elaborated." Prof. Dr. Christiane Schmullius   "The PhD thesis written by Mr. Ackermann is an excellent and very comprehensive work performed at the highest scientific level. It examines in detail the potential of SAR data with regards to the derivation of forest stem volume in the temperate latitudes. The work belongs to a technically complex field. Nevertheless, Mr. Ackermann has succeeded in presenting the content in a clear and understandable way." Dr. Christian Thiel   "The proposed document is overall of very good quality. Mr. Ackermann has done an exhaustive analysis of the in-situ data available on the Thuringian forest and was able to derive Growing Stocking Volume using L- and X-band spaceborne SAR data. The document is very well structured with a good split of information between the core of the text presented in the 6 chapters and the 4 annexes, which contain detailed results. Mr. Ackermann's English grammar is excellent and his syntax is crystal clear, making his document pleasant to read. The way arguments are presented is logical and Mr. Ackermann gives a lot of attention to ensuring that sound explanations properly support these arguments." Dr. Maurice Borgeaud.